Multiscalar Narratives of a Disaster: From Media Amplification to Western Participation in Asian Tsunamis - Bonati, Sara (Culture Unbound, 2015)
The international recovery system responds differently to disasters with similar characteristics. It answers to specific motivations that are not necessarily connected to the nature of the disaster. The variability of the answers given not only depends on the type of disaster but also, in particular, on the local social structure and on the transcalar narrative of the disaster used to move communities not directly affected to action. This paper therefore analyses the level of Western involvement in two Asian tsunami recovery plans and the role of the media in attracting Western private donations. To this end, Italian involvement in the two cases is discussed. Beginning with a literature review to support the argument that the media are crucial in stimulating private participation through ‘spectacularizing’ the disaster, this paper illustrates that, when spectacularization is insufficient, the media additionally adopts the strategy of ‘transposition’, leading to ‘appropriation’ of the event. In particular, during the Boxing Day tsunami of 2004, the transposition became the ‘Westernization’ of the narrative of the disaster. The process of transposition or Westernization, however, did not happen with the same modalities in the narrative of the Tohoku tsunami of 2011. In this case, the focus was more on the technological disaster that followed the natural disaster. The author concludes that emotional transposition of the disasters by the media played an important role in stimulating private donations and in spurring governmental relief in both the disasters. Foreign governments, however, are mainly moved by other factors such as ‘flag policy’ or what Olsen et al. (2004) identified as the concept of ‘donor interests’.